1979
DOI: 10.1111/j.1365-2222.1979.tb02489.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma: a comparative study of urban and rural Xhosa children

Abstract: Summary An epidemiological study was undertaken to determine the prevalence of asthma in young urban and rural black (Xhosa) children. One thousand three hundred and seventy five children were studied, 694 from a Cape Town african township and 671 from a rural area in Transkei. The exercise tolerance test which required free range running at maximum effort for 6 min was used to identify asthmatic subjects. A fall of 15% or more in the post‐exercise FEV1 and PEFR values was regarded as a positive result. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
4
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(120 citation statements)
references
References 15 publications
(10 reference statements)
8
104
4
2
Order By: Relevance
“…It was then centrifuged at 3000 rpm for 5 minutes. Supernatant was removed and transferred to new tube for repetition with changes in lifestyle [12][13] and this is supported by studies which have shown an increased prevalence of asthmatic symptoms among people who have moved from a traditional to a more westernized style of living [14][15][16][17]. The disease is now reaching epidemic proportions in westernized countries.…”
Section: Preparation Of Pah Samplesmentioning
confidence: 82%
“…It was then centrifuged at 3000 rpm for 5 minutes. Supernatant was removed and transferred to new tube for repetition with changes in lifestyle [12][13] and this is supported by studies which have shown an increased prevalence of asthmatic symptoms among people who have moved from a traditional to a more westernized style of living [14][15][16][17]. The disease is now reaching epidemic proportions in westernized countries.…”
Section: Preparation Of Pah Samplesmentioning
confidence: 82%
“…In addition, several studies, most performed in the Tropics, have provided further evidence that atopic disorders occur more commonly among individuals living in urban, more affluent and westernized areas as compared with those living in rural areas with traditional lifestyle (22)(23)(24)(25)(26). As to sub-Saharan Africa, the situation appears to be more complex.…”
mentioning
confidence: 99%
“…Migrants who go from villages to towns have more asthma (55,56); asthma is less prevalent in crowded conditions (57); and asthma is very rare in populations with traditional, nonaffluent lifestyles (15,58).…”
Section: Australia -Children 8 -11 Yrsmentioning
confidence: 99%